Detection of Heavy Metal Ions in Different Samples of Water near Pen-Khopoli (Maharashtra) - Sonawane, V.Y. (Asian Journal of Chemistry, 2010)
Seven metallic parameters in drinking water from seven samples of different places near Penkhopoli (Maharashtra). India were monitored for six months and values obtained were compared with standards prescribed by Indian Council of Medical Research (ICMR) and World Health Organization (WHO).